2006
DOI: 10.1159/000094222
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary marker chromosome 5 diagnosed by M-FISH in a child with congenital heart defect and unusual face

Abstract: We describe a female patient with a small supernumerary marker chromosome (sSMC) present in mosaic and characterized in detail by fluorescence in situ hybridization (FISH) using all 24 human whole chromosome painting probes, multicolor banding (MCB) and subcentromere specific multicolor FISH (subcenM-FISH). The sSMC was demonstrated to be derived from chromosome 5 and the karyotype of our patient was as follows: 47,XX,+mar.ish r(5)(::p13.2∼p13.3→q11.2::) [60%]/46,XX [40%]. Partial trisomy for the proximal 5p a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 73 publications
(48 reference statements)
3
12
0
Order By: Relevance
“…1 ). It is striking to note the facial resemblance of our patient with 2 well-illustrated cases, namely patient 3 in Stankiewicz et al [1999] and patient 6 in Sarri et al [2006], carrying der(5)(p14q11.2) and der(5)(p13.3q11.2), respectively. Of note, similar craniofacial features were precisely described in an adult male with a de novo dup(5)(p13.1p13.2) [Oexle et al, 2011].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…1 ). It is striking to note the facial resemblance of our patient with 2 well-illustrated cases, namely patient 3 in Stankiewicz et al [1999] and patient 6 in Sarri et al [2006], carrying der(5)(p14q11.2) and der(5)(p13.3q11.2), respectively. Of note, similar craniofacial features were precisely described in an adult male with a de novo dup(5)(p13.1p13.2) [Oexle et al, 2011].…”
Section: Discussionsupporting
confidence: 55%
“…An influence on the phenotype by the genetic material of the long arm of chromosome 5q10q12 is unlikely or minimal as discussed elsewhere [Douyard et al, 2006;Melo et al, 2011]. Accordingly, previous authors describing sSMC(5) containing both proximal 5p and 5q regions focused on the contribution of the proximal 5p region to the phenotype [Stankiewicz et al, 1999;D'Amato Sizonenko et al, 2002;Sarri et al, 2006]. To the best of our knowledge, only 6 other patients with sSMC(5) containing the proximal p10p13.1 region are described in detail ( Table 1 ) [ Avansino et al, 1999;Masuno et al, 1999;Stankiewicz et al, 1999;D'Amato Sizonenko et al, 2002;Sarri et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the case published by Ohashi et al [2011] had a complex duplication/deletion rearrangement and the triplicated segment in the patient reported by Melo et al [2011] was assigned exclusively to the long arm, these 2 reports were not considered. Finally, 7 cases were enrolled for further evaluation: Avansino et al [1999], Schuffenhauer et al [1996], Stankiewicz et al [2000], D'Amato Sizonenko et al [2002] (2 cases), Liehr et al [2006], and Sarri et al [2006]. Although significant trisomy of the proximal long arm of chromosome 5 could be identified in the ring of the patient observed by Stankiewicz et al [2000], in case 2 of D'Amato Sizonenko et al [2002], and that by Sarri et al [2006], and, in addition to sSMC 5, a deletion of 5p was also identified by Schuffenhauer et al [1996], these 4 cases were included in the evaluation.…”
Section: Discussionmentioning
confidence: 99%